Assessment of the Budget Balance and Public Expenditure in The European Union Countries Against the Background of The Macroeconomic Situation in The Face of The Coronavirus Crisis - Magdalena GORSKA; Pawel BLASZCZYK; Katarzyna LASINSKA; Rafal KIESZEK (Communications of International Proceedings, 2021)
The basic aim of this study is to assess the selected aspects of the fiscal situation of EU countries, including budget balances and expenditures against the background of their macroeconomic condition in view of the coronavirus epidemic. An attempt is also made to answer the following questions: what was the impact of the significant deterioration of the macroeconomic situation in the crisis conditions of EU countries on the fiscal sphere and what was the reaction of decision-makers with regard to budget expenditures? The study consists of three main parts. The first one outlines the research methodology based on a modified version of the misery index. As a consequence, a proprietary macroeconomic condition index (MCI) is put forward. In the second part, the macroeconomic assessment of the EU countries in the 2015-2020 period was performed using the MCI. In view of the above, the third part analyses the balance and expenditures of the public finance sector with the coronavirus in mind. The results of the research indicate that it cannot be clearly stated to what extent the support of the fiscal authorities in the form of increased public spending may be seen as a "cure" for the coronavirus crisis. More research is still needed in this area, employing statistical and econometric methods. The authors hope that this study will contribute to further, in-depth research on the effects of the coronavirus on the macroeconomic and fiscal spheres in the European Union, with particular emphasis on the sphere of budgetary expenditures.
Keywords: budget; coronavirus crisis